Identifying distinct phenotypes of patients with juvenile systemic lupus erythematosus: results from a cluster analysis by the Egyptian college of rheumatology (ECR) study group - Nevin Hammam; Tamer A Gheita; Ali Bakhiet; Mohamed Bakry Mahmoud; Rasha El Owaidy; Hend Abdel Nabi; Ahmed M Elsaman; Iman Khalifa; Abeer M Nour ElDin Abd ElBaky; Faten Ismail; Eman Hassan; Rawhya R El Shereef; et al. (BMC, 2024)
Abstract Purpose Juvenile systemic lupus erythematosus (J-SLE) is a complex, heterogeneous disease affecting multiple organs. However, the classification of its subgroups is still debated. Therefore, we investigated the aggregated clinical features in patients with J-SLE using cluster analysis. Methods: Patients (≤ 16 years) diagnosed using the Systemic Lupus International Collaborating Clinics (SLICC) classification criteria were identified from the clinical database of the Egyptian College of Rheumatology (ECR) SLE study group. Demographic data, clinical characteristics, laboratory features, and current therapies were selected. A cluster analysis was performed to identify different clinical phenotypes. Results: Overall, 404 patients, of whom 355 (87.9%) were female, had a mean age at diagnosis of 11.2 years and a mean disease duration of 2.3 years. We identified four distinct subsets of patients. Patients in cluster 1 (n = 103, 25.5%) were characterized predominantly by mucocutaneous and neurologic manifestations. Patients in cluster 2 (n = 101, 25%) were more likely to have arthritis and pulmonary manifestations. Cluster 3 (n = 71, 17.6%) had the lowest prevalence of arthritis and lupus nephritis (LN), indicative of mild disease intensity. Patients in cluster 4 (n = 129, 31.9%) have the highest frequency of arthritis, vasculitis, and LN. Cluster 1 and 4 patients had the highest disease activity index score and were less likely to use low-dose aspirin (LDA). The SLE damage index was comparable across clusters. Conclusions: Four identified J-SLE clusters express distinct clinical phenotypes. Attention should be paid to including LDA in the therapeutic regimen for J-SLE. Further work is needed to replicate and clarify the phenotype patterns in J-SLE.